y+2= -3(x-1) how do I solve.?

For standard form, you want to write the x-term first, followed by the y-term. Most textbooks want the constant on the left, while others prefer it on the right side of the equal sign. Double check what YOUR textbook wants. Your answer should look like: some number times x plus(or minus) some number times y plus (or minus) a number =0.

y+2 = -3(x-1)

First, distribute the -3 across the parenthesis. You should have y + 2 = -3x + 3. Next, we need to get all the terms on the right hand side of the equal sign. So add +3x to both sides and subtract the 3 from both sides.

Now you have y + 2 +3x -3 = 0. Remember that addition is commutative, so write the terms in the order 3x + y + 2 -3 = 0. Combine like terms for the final answer ...

**3x + y -1 = 0**. (If you have one of those professors or textbooks that wants the constant term on the right, simply add 1 to both sides and get 3x + y = 1.)